Coping Strategies to Increase Adolescent Emotional Intelligence in the Pandemic Covid-19 - Irfan Fahriza; Syari Fitrah Rayaginansih; Eko Rismara Agustina (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2020)
The present study aimed to discover the effectiveness of coping strategies to improve student’s emotional intelligence in MA Asy-Syfa Cipatat during the Covid-19 Outbreak. The study used a quasi-experimental method with a nonequivalent control group design. The thirty-eight students were involved in this study, determined using total sampling. The data were collected using questionnaires and analyzed using a t-test. The present study exhibited that coping strategies are effective to improve the emotional intelligence of students MA Asy-Syfa.